Engaged science - Blaauw, Kyran Phil (Rhodes University, 2026)
This study investigates how media could foster engagement between sugarcane growers, extension officers, and scientists around a genetically modified variety of sugarcane. The research focused on two research sites in the north and south coasts of KwaZulu-Natal (KZN), where both small-scale and commercial sugarcane growers were interviewed. Using participative action research methodology, the researcher developed and tested various multimedia materials – specifically animated explainer videos and an accompanying information booklet. These materials were shaped by various interactions with both growers and scientists, including questionnaires, individual and focus group interviews, ensuring that the content would both be scientifically accurate and aligned with the concerns of grower communities. The study aimed to establish their foundational understanding of GM products and identify the specific concerns that growers had regarding adopting GM crops. The research sought to create media resources to serve as an entry point for growers interacting with the GM sugarcane variety to foster engagement. The materials were tested through focus group discussions with growers, providing direct feedback on their effectiveness in conveying key information, addressing concerns, and fostering a constructive dialogue among stakeholders. The feedback was analysed to identify areas for improvement. The analysis revealed several recurring themes and concerns, including limited land availability, scepticism towards GM crops, environmental concerns, and the necessity for clear and effective communication channels between scientists, extension officers, and growers. The thematic analysis underscored the critical role of tailored media and communication strategies in successfully introducing GM crops to different grower communities. It became evident that creating media content that speaks to growers’ specific concerns while presenting balanced information is crucial in overcoming barriers to adopting GM technologies. The insights suggest that effective communication and engagement strategies must be responsive to the local context, address environmental and economic concerns, and provide a platform for continued dialogue among all stakeholders. The findings emphasise that communication strategies must be nuanced, context-specific, and inclusive, particularly in areas where small-scale and commercial farmers are present, and their needs may differ. Media produced: This praxis thesis is accompanied by a series of media products that form an integral part of the research. These materials consist of four videos and two informational booklets, each designed to convey key concepts related to genetically modified (GM) sugarcane in an accessible manner. The first video is an animated production that provides a foundational explanation of genetically modified organisms (GMOs) and their relevance to developing a genetically modified sugarcane variety. The second video outlines growers’ responsibilities should they adopt the GM sugarcane variety developed by the South African Sugarcane Research Institute (SASRI). These videos have also been produced in isiZulu to ensure accessibility for a wider audience. In addition to the videos, an informational booklet has been developed, presenting the same content in written form. This booklet has also been translated into isiZulu. These media products were developed to provide clear, practical, and engaging explanations of the subject matter. They aim to facilitate a broader understanding of and engagement around genetically modified sugarcane. https://drive.google.com/drive/folders/1nJU41vo0HGPu5OVckf0Itm5LxFGOMnNt?usp=sharing
multimedia as a tool for engagement between researchers and growers on GM sugarcane
Keywords: Transgenic plants; Genetically modified sugarcane; Action research; Communication for development; Journalism